Tingkat Kesehatan Bank: Pendekatan Risk Based Bank Rating terhadap Nilai Perusahaan - Juli Murwani; Abd Rohman Taufiq (Owner : Riset dan Jurnal Akuntansi, 2022)
Conventional National Private Banks as one of the companies that contribute to stabilizing the national economy need to maintain their health level by implementing various applicable policies. To maintain the soundness of the bank, it must be able to stabilize its performance so that it has an impact on the trust of stakeholders in the bank. Thus the purpose of banking will be fulfilled, namely to maximize the value of the company. This research was conducted at Conventional National Private Commercial Banks listed on the IDX 2016-2020. The data source is secondary data obtained from the annual report of each bank which is the sample of the study as many as 32 banks. The research method used is a quantitative approach using multiple linear regression analysis and using SPSS version 18 program assistance. The results of this research are GCG variable with independent commissioner board size proxy, profitability with BOPO ratio has no effect on firm value. While the risk profile using the LDR ratio, capital as measured by the CAR ratio has an effect on firm value. The variable size of the bank is not able to moderate the effect of GCG on firm value.